THE INFLUENCE OF SOCIAL SUPPORT AND OPTIMISM ON STUDENT SELF-EFFICACY IN MEMORIZING THE QURAN AT SMPIT AL FAKHRI SINGGAL - Adinda Dwi Cahya Pohan; Nuraini; Yudistira Fauzy Indrawan (RADJA PUBLIKA, 2023)
This study aims to determine the effect of social support and optimism on students' self-efficacy in memorizing the Koran at SMPIT Al-Fakhri Sunggal. The population of this research is 222 students. Sampling in this study was carried out using a purposive technique, namely taking samples based on certain characteristics. In this study, the sample characteristics were students who had parents, so the sample size was 209 students. This research uses quantitative methods. Measuring tools used are social support scale, optimism scale and self-efficacy scale. Data analysis using multiple linear regression test. The results of this study indicate that there is a significant influence of social support on student self-efficacy, where the coefficient value is 1. 277 and a significance value of 0.000, namely <0.05, the hypothesis is accepted. Furthermore, the results of the study also show that there is a negative effect of optimism on student self-efficacy at SMPIT Al-Fakhri with a coefficient value of -0.732 and a significance value of 0.000 <0.05. Based on this research, it was obtained data that social support and optimism simultaneously affect self-efficacy with F count > F table F count = 1.073 > F table = 3.89.